Intercultural Alliances : Critical Transformation. - Collier, Professor Mary Jane Jane (International and intercultural communication annual., 2002)
Intercultural Alliances, Volume 25 of The International and Intercultural Communication Annual, reflects the struggle to comprehend our international communities and improve the ways in which we communicate and negotiate across cultures. Carefully organized and edited by Mary Jane Collier, this accessible volume defines intercultural alliances and demonstrates their potential through examples of effective and ineffective alliances. A group of diverse and distinguished contributors presents an array of approaches to intercultural alliances, analyzing relationships between groups and individu.